Spinal dysraphisms in the parturient: implications for perioperative anaesthetic care and labour analgesia. Issue 3 (August 2015) - Murphy, C.J.; Stanley, E.; Kavanagh, E.; Lenane, P.E.; McCaul, C.L.
Highlights Spinal dysraphisms are among the most common neurodevelopmental anomalies. Bony and neural structures may be anatomically abnormal. Neuraxial blocks are possible in selected patients. The incidence of complications and failure is relatively high. Magnetic resonance imaging can clarify anatomical abnormalities and assist decision making regarding neuraxial techniques.